Bleb geometry and morphology after Preserflo Microshunt surgery: Risk factors for surgical failure. - Marta Ibarz Barberá; Jose Luis Hernández-Verdejo; Jean Bragard; Laura Morales-Fernández; Lola Rodríguez-Carrillo; Fátima Martínez Galdón; Pedro Tañá; Miguel A Teus (PLoS ONE, 2023)
Purpose To investigate the possible risk factors for treatment failure in patients who had undergone Preserflo Microshunt (PMS) implantation, using anterior-segment optical coherence tomography (AS-OCT) to analyze the internal structures of the bleb. Methods The PMS blebs of 54 patients were evaluated with AS-OCT. A mathematical model was used to calculate the total filtering surface of the episcleral fluid cavity (EFC) and the hydraulic conductivity (HC) of the bleb wall. Complete and qualified success were defined as IOP between 6 and 17 mmHg with or without glaucoma medication. The relation between baseline characteristics and probability of bleb success was analyzed by bivariate and multivariate logistic regression. The main outcome measures were mean bleb wall thickness (BWT), reflectivity (BWR), HC, mean horizontal and vertical diameter and total filtering surface (TFS) of the EFC. Results Blebs from 74% patients were considered as complete success and 26% as failure. BWR and BWT increased linearly up to the first year in both groups. BWR was higher in the group failure (p = 0.02) and BWT in the group success (p<0.001). EFC was wider and shorter in the success group (p = 0.009, p = 0.03). Higher TFS showed a negative correlation with IOP (r = -0.4, p = 0.002). Higher baseline IOP was associated with success of PMS by multivariate analysis (p = 0.01). Mean HC, 0.034 ± 0.008 (μL/min)/mm2/mmHg, was negatively correlated with bleb surface (r = -0.5, p<0.0001) and wall´s thickness (r = -0.3, p = 0.01). Conclusions AS-OCT revealed that successful PMS blebs could show either thick hyporreflective walls or wide filtering surfaces with thin capsules. A higher baseline IOP increased the probability of surgical success.